The dual trend of diffusion of heavy rare earth elements during the grain boundary diffusion process for sintered Nd-Fe-B magnets. (15th April 2018) - Wu, Binghui; Ding, Xuefeng; Zhang, Qingke; Yang, Lijing; Zheng, Bizhang; Hu, Fangqin; Song, Zhenlun
Abstract: Diffusion of heavy rare earth elements (HREEs, Tb and Dy) after being coated on sintered Nd-Fe-B magnets by direct current magnetron sputtering was investigated. The results reveal that gain of the coercivity shows a higher efficiency of HREE consumption compared with other coating methods. The HREE diffuses along the grain boundary phase (GBP) deep into the magnet, an HREE-rich shell forms at the superficial layer of the diffused Nd2 Fe14 B grains, and the HREE in the magnets shows a dual-trend distribution. The diffusion of HREE includes a fast diffusion in the GBP and a slow diffusion in the grain phase (GP). Graphical abstract: Unlabelled Image